2012
DOI: 10.1371/journal.pone.0048838
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Kinetic Properties of Two Acetylcholinesterases from the Western Honey Bee, Apis mellifera

Abstract: We investigated the molecular and kinetic properties of two acetylcholinesterases (AmAChE1 and AmAChE2) from the Western honey bee, Apis mellifera. Western blot analysis revealed that AmAChE2 has most of catalytic activity rather than AmAChE1, further suggesting that AmAChE2 is responsible for synaptic transmission in A. mellifera, in contrast to most other insects. AmAChE2 was predominately expressed in the ganglia and head containing the central nervous system (CNS), while AmAChE1 was abundantly observed not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 47 publications
5
73
1
Order By: Relevance
“…These findings strongly support that AChE1 plays a major role in cholinergic functions, and is the major target of anticholinesterase insecticides. However, more recent studies revealed that some insects express AChE2 as the major catalytic enzyme, rather than AChE1 [28,37,38]. Although the ability of AChE2 to function as a major catalytic enzyme does not necessarily indicate either its major function in cholinergic neurotransmission or as a major target for OP and CB insecticides, it would be interesting to investigate if AChE2 is a major enzyme responsible for cholinergic neurotransmission and serves as a major target for these insecticides by RNAi.…”
Section: Identification or Validation Of Insecticide Target Genesmentioning
confidence: 99%
“…These findings strongly support that AChE1 plays a major role in cholinergic functions, and is the major target of anticholinesterase insecticides. However, more recent studies revealed that some insects express AChE2 as the major catalytic enzyme, rather than AChE1 [28,37,38]. Although the ability of AChE2 to function as a major catalytic enzyme does not necessarily indicate either its major function in cholinergic neurotransmission or as a major target for OP and CB insecticides, it would be interesting to investigate if AChE2 is a major enzyme responsible for cholinergic neurotransmission and serves as a major target for these insecticides by RNAi.…”
Section: Identification or Validation Of Insecticide Target Genesmentioning
confidence: 99%
“…However, ace2 showed relative more high expression than ace1 in some insects, e.g. Bombyx mori [4] and was confirmed as the major catalytic enzyme in synaptic transmission in Apis mellifera [5]. In our previous studies, two ace genes (Ppace1 and Ppace2) were cloned from the pond wolf spider Pardosa pseudoannulata, an important predatory enemy against several insect pests in most parts of Asia and showed different sensitivities to organophosphate and carbamate insecticides, when compared to some insect pests, such as the rice pest Nilaparvata lugens [6].…”
Section: Introductionmentioning
confidence: 98%
“…Some authors have ruled out the presence of BChE in insects (see KIM et al 2012), whereas others measured its activity (DE VILLAR et al 1980;KULIEVA et al 1995). Recent research has validated the hypothesis proposed by GNAGEY et al (1987) who argued that insects possess AChE with substrate specificity that occupies the mid range between vertebrate AChE and BChE.…”
Section: Discussionmentioning
confidence: 99%
“…The above could be attributed to the fact that AChEs in insects are coded by two genes, ace 1 and ace 2, whose products, enzymes AChE1 and AChE2, have different functions (LI & HaN 2002;KIM & LEE 2013;XIAO et al 2014). KIM et al (2012) demonstrated that AChE2 is the key neurotransmission enzyme in honey bees. AChE1 probably has nonneuronal functions and protects bees against the harmful effects of xenobiotics, therefore, it plays a similar role to vertebrate BChE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation